Tantangan Pendidikan Tinggi Hukum di Masa Pandemi Covid-19 dalam Pemanfaatan Teknologi: Challenges of Higher Legal Education in the Covid-19 Pandemic Period in Utilizing Technology - Prasetyani, Aprilia Evy (Fakultas Hukum Universitas Negeri Semarang, 2021)
Covid-19 Pandemic is a health threat that occurs globally and affects many aspects of life. UNESCO (2020) reported that by the end of 2019, COVID-19 has spread to all countries in the world and caused deaths. There are various attempts promoted to cut the spread of the virus. One of them is to shut schools and universities down. The growth of technology in education until today gives a colour variation in the learning process. There are some reasons why higher law education must react to the rapid change of society during this Covid-19 pandemic period. The development of law could not follow the speed of change that is happening mainly due to the political issue. Whereas higher law education is supposed to take a crucial role to face the growth of law practice that requires solutions and new ideas. The world of Law (Practitioners and Mostly Academics) is naturally opened towards science and technology contribution. The reason is that there is a growing need and demand to develop a legal reform program. Information Technology can be employed to support and assure good governance, administration, and judicial process. The good and bad sideof law practice can be traced from the teaching of law in law higher education. At present, the science of law can no longer be confined to the academic romanticism of the past which is still being enforced by rigid and inflexible higher education administrative bureaucratic regime. It is only when legal law scientists can collaborate massively with other scientists, government institutions, industries and community figures, the existence of law and legal science will be benefitted by the seekers of justice.